2014
DOI: 10.1002/jmv.23946
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of circulating pandemic strains of influenza A virus during 2012 to 2013 in Lucknow (India)

Abstract: The pandemic H1N1 strain of Influenza A virus [A(H1N1)pdm09] is now well adapted in human populations. However, it is still causing sporadic outbreaks worldwide with different severity. The present study was planned to understand the genetic diversity (based on the HA1 gene) of influenza A(H1N1)pdm09 strains circulating during the post pandemic period. The HA1 gene was selected because the HA1 protein is immunogenic, functions as a receptor binding site and indirectly affects transmission and pathogenicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Molecular analysis at gene level (especially HA1 and NA genes) identified few mutational changes which were different from the previously circulating strains of pH1N1 virus as described earlier [6,10]. Mutational changes in the active site of HA1 protein showed 5 mutations, similar to previously circulating pH1N1 strains of Indian region along with 3 new mutations in 2015 strains at different positions (D185N, D213N, and H290Q) [11].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Molecular analysis at gene level (especially HA1 and NA genes) identified few mutational changes which were different from the previously circulating strains of pH1N1 virus as described earlier [6,10]. Mutational changes in the active site of HA1 protein showed 5 mutations, similar to previously circulating pH1N1 strains of Indian region along with 3 new mutations in 2015 strains at different positions (D185N, D213N, and H290Q) [11].…”
Section: Discussionsupporting
confidence: 54%
“…According to Indian health officials, the pH1N1 strain has not changed much from the first strain that emerged in 2009 [20]. The phylogenetic analysis based on partial HA1 gene sequences of study strains revealed the presence of 2 mutations (S220T and S202T) in HA1 gene of all study strains which are specific to clade 7 genotype of pH1N1 [6,10,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transient mutation, also called an ''adaptive mutation'', may be the consequence of individual mutations that relieve the selective pressure caused by survival [11]. The K180Q mutation was (at least, in the Beijing area) a novel substitution within the Sa antigenic site of the H1 segment; this mutation has also been observed in Peru and India since 2013 [9,26]. In H3, three amino acid mutations were detected at two antigenic sites (A and B); these substitutions were observed in 2012-2013, but at a lower frequency [10].…”
Section: Discussionmentioning
confidence: 99%
“…One strand complementary DNA (c‐DNA) was synthesized in two separate eppendorfs using the HA and the NA gene‐specific primers by the method as described previously [Dangi et al, ]. Two step conventional reverse transcription PCR (RT‐PCR) was done to amplify viral c‐DNA specific for 824 bp fragment (nucleotide position 360–1184) in the HA1 domain and 931 bp fragments (nucleotide position 367–1298) in the NA gene [Hoffmann et al, ; Chutinimitkul et al, ].…”
Section: Methodsmentioning
confidence: 99%